Geoffrey Bartlett - Bartlett, Geoffrey, 1952-; Hurlston, David; Wach, Kenneth; National Gallery of Victoria (Melbourne, Vic. : National Gallery of Victoria, 2007)
This exhibition catalogue accompanies an exhibition of the same name. It traces the work of this Australian sculptor over the last 20 years following attendance at a major American university through the aid of a scholarship.
Catalogue of an exhibition held at the National Gallery of Victoria, Melbourne, 21 July - 14 October 2007.
Includes bibliographical references.
Keywords: Bartlett, Geoffrey, -- 1952- -- Exhibitions